Omnino: VSU Undergraduate Research Journal. 2012-2013 - Miller, Ashley M.; Pyles, Micah; Ellis, Meagan; Hanna, Laura N.; Dandron, Jennifer; Grady, Charlotte; Lipsky, Alex; Lively, Sarah; Bradley, Rachel L.; Sobhani, Melody; Milam, John; Butler, Lakesha; et al. (Valdosta State University, 2013)
Dominance: The Study of White Representation in Disney's The Princess and the Frog Ashley M. Miller; Corporate-led Globalization: Colonizing the Last Frontier Micah Pyles; Focalization and Proletarian Gender Dynamics in Steinbeck's "The Chrysanthemums" Meagan Ellis; American Pop Culture and the Formation of Identity in Hanif Kureishi's The Black Album Laura N. Hanna; The Relationship between the Media and School Shootings in the Past Fifteen Years, with Regards to the Columbine, Virginia Tech, and Newtown Massacres Jennifer Dandron; They Bleed on Both Sides Charlotte Grady; The Importance of the Themes in Tchaikovsky's Violin Concerto in D Major, Op. 35, Movement I Alex Lipsky; Fluency and Guided Repeated Oral Reading Sarah Lively; Effects of Collaboration on Academic Performance: Cognitive Load Theory as an Integral Component of Group Learning Rachel L. Bradley; Copper Complexes as a Delivery Agent for Medicinal Agents Melody Sobhani, John Milam, Lakesha Butler, David Jenkins, Iris Rivera, Satilla Johns, Rebekah Graham, Haley Franklin, Dustin Jenkins; The 2012 Charter Schools Constitutional Amendment in Georgia: A County level Analysis of the Election Results Christopher John May; Effects of Locus of Control and Dream Recall Training on Dreaming Crystal Logan; BOOK REVIEWS The Cambridge Introduction to George Orwell by John Rodden and John Rossi Reviewed by Erica Even; Witches, Wife Beaters, & Whores Common Law and Common Folk in Early America by Elaine Forman Crane Reviewed by Megan Shelton;
I am very pleased to introduce volume 3 of Omnino, VSU's under- graduate research journal.This year, Omnino once again offers an impres- sive body of student research, all of which has been rigorously peer-reviewed by VSU faculty members and edited by VSU undergrad- uates. We are particularly proud of the wide array of disciplines repre- sented in our pages. In fact, Omnino received an unprecedented thirty-two student submissions this year, thanks to the hard work of the Omnino managing and student editors who reached out to faculty and students, sent emails, handed out fliers, posted signage, and made nu- merous in-person presentations in classes. This outreach paid off, and we are pleased to publish a robust and diverse array of high-quality un- dergraduate scholarship this year, stemming from nine different disci- plines: Chemistry, Communication Sciences and Disorders, English, Music, Philosophy, Political Science, Psychology, Sociology, and The- atre/Dance. Next year, we would like to see even more students from more departments submit their work to Omnino. In addition to the hard work of the Omnino managing and student editors, I would also like to extend my sincere gratitude to the dozens of VSU faculty members who read, reviewed, and provided feedback on this year's Omnino submissions. The editors and I appreciate you taking the time out of your already busy schedules to provide this invaluable feedback, without which, none of this would be possible.
Keywords: College students' writings; Research; Periodicals; Interdisciplinary research; Georgia